Securing the commons - Meinzen-Dick, Ruth S.; Mwangi, Esther; Dohrn, Stephan (International Food Policy Research Institute, 2006)
This brief addresses the question: What are the commons and what are they good for? The authors put forth the following policy implications: (1.) Devolving authority to the lowest levels possible can improve the effectiveness of the management of common pool resources, if the state is willing and able to back the rules established at those levels. (2.) State recognition of common property systems is essential to enable those who depend on the commons to reap the benefits from these areas. (3.) Strengthening individual property rights can undermine the existence of the commons. (4.) Devising strategies and mechanisms to strengthen group institutions, and making sure they are accountable and transparent for all members, can increase overall security of the commons. (5.) Fostering innovative ways to diversify the livelihoods of commons users can help reach both equity and environmental stewardship objectives. (6.) Securing the commons requires empowering local communities to deal with outsiders.